Education in Spain: Decalogue of errors (Journal of Parents and Teachers, 2012)
This article analyses the socio-educational mistakes that, according to the author, are the most significant as key factors in order that the Spanish educational system is not giving the results that our society deserves. d Española de EURYDICE. Miembro de TEAM-EUROPA, de conferenciantes expertos de la Comisión Europea. Subdirector de la Revista Española de Educación Comparada.
Keywords: Education system; Education Policy; Parental responsibility; review; opinion